Assessment of variability in physical and chemical composition of Cuminum cyminum seeds from arid and semiarid India - DUBEY, P N; SAXENA, S N; MISHRA, B K; AISHWATH, O P; SOLANKI, R K; SINGH, BALRAJ; LAL, G (The Indian Journal of Agricultural Sciences, 2016)
Cumin (Cuminum cyminum L.) is an important spice commodity cultivated under large areas in arid and semiarid India. It has attained a valuable importance due to its immense aromatic, culinary and medicinal values. Due to its very selective dry and cool climate requirement, cumin is mainly being grown in western regions of India. The present study accounts for the variability observed in physical and chemical properties of cumin seed samples collected from cumin growing areas located in the 7 districts of Rajasthan and 5 districts of Gujarat classified under Agro-Ecological Sub Regions (AESR) of India. Quantity of essential oil (EO) in cumin seeds from various districts revealed that the overall EO content ranged between 28.4 to 39.1 g/kg. In Rajasthan, highest EO content was recorded in the cumin samples from Nagaur (38.5 ± 0.37), followed by Jaisalmer (37.4 ± 0.31) and was least in Ajmer (28.6 ± 0.27) whereas, in Gujarat, samples from Patan possessed highest EO content (39.1± 0.17) with least values in Amreli (28.4 ±1.08). The average flavonoid content expressed as mg QE/g seeds was highest in Nagaur (39.72), followed by Amreli (36.03) and lowest in Ajmer district (23.71), similarly the estimated phenol content (mg GAE/g seeds) was maximum in Jalore (73.61), followed by Nagaur (63.77) and least in Amreli district (41.50). The carbohydrates content and total protein content ranged between 15.86-28.88 and 19.30-21.89 per cent respectively. This study also provides basic information in understanding cumin composition and its value as a commodity for business based on interstices parameters reflecting quality assessment for regional produce harvested from India.